Some number arrays related to Pascal and Lucas triangles - Pita-Ruiz, Claudio (My University, 2013)
By taking repeated convolutions of the sequence n p with the constant sequence 1, we form the number arrays of the coefficients resulting when we write the mentioned convolutions as linear combinations of certain binomial coefficients. According to this procedure, Pascal and Lucas triangles correspond to the cases p = 1 and p = 2 respectively. We show that these arrays have some properties similar to the well-known properties of Pascal and Lucas triangles.